A trans‐omics assessment of gene–gene interaction in early‐stage NSCLC. Issue 1 (5th December 2022) - Chen, Jiajin; Song, Yunjie; Li, Yi; Wei, Yongyue; Shen, Sipeng; Zhao, Yang; You, Dongfang; Su, Li; Bjaanæs, Maria Moksnes; Karlsson, Anna; Planck, Maria; Staaf, Johan; et al.
Abstract : Epigenome‐wide gene–gene (G × G) interactions associated with non‐small‐cell lung cancer (NSCLC) survival may provide insights into molecular mechanisms and therapeutic targets. Hence, we proposed a three‐step analytic strategy to identify significant and robust G × G interactions that are relevant to NSCLC survival. In the first step, among 49 billion pairs of DNA methylation probes, we identified 175 775 G × G interactions with P Bonferroni  ≤ 0.05 in the discovery phase of epigenomic analysis; among them, 15 534 were confirmed with P  ≤ 0.05 in the validation phase. In the second step, we further performed a functional validation for these G × G interactions at the gene expression level by way of a two‐phase (discovery and validation) transcriptomic analysis, and confirmed 25 significant G × G interactions enriched in the 6p21.33 and 6p22.1 regions. In the third step, we identified two G × G interactions using the trans‐omics analysis, which had significant ( P  ≤ 0.05) epigenetic cis ‐regulation of transcription and robust G × G interactions at both the epigenetic and transcriptional levels. These interactions were cg14391855 × cg23937960 ( β interaction  = 0.018, P  = 1.87 × 10 −12 ), which mapped to RELA  ×  HLA‐G ( β interaction  = 0.218, P  = 8.82 × 10 −11 ) and cg08872738 × cg27077312 ( β interaction  = −0.010, P  = 1.16 × 10 −11 ), which mapped to TUBA1B  ×  TOMM40 ( β interaction =−0.250, P  = 3.83 × 10 −10 ). A trans‐omics mediation analysis revealed that 20.3% of epigenetic effects on NSCLC survival were significantly ( P  = 0.034) mediated through transcriptional expression. These statistically significant trans‐omics G × G interactions can also discriminate patients with high risk of mortality. In summary, we identified two G × G interactions at both the epigenetic and transcriptional levels, and our findings may provide potential clues for precision treatment of NSCLC. Abstract : A three‐step, trans‐omics study identified two gene–gene interactions, cg14391855 × cg23937960 (mapped to RELA  ×  HLA‐G ) as well as cg08872738 × cg27077312 (mapped to TUBA1B  ×  TOMM40 ), which were significantly and robustly associated with NSCLC survival at both the epigenetic and transcriptional levels. Our findings have implications of precision treatment by providing therapeutic targets for early‐stage NSCLC patients.